Efficient routing algorithms for anycast routing - Tan, Choon Leng. (2008)
In this research project, we proposed three anycast routing heuristics: the shortest widest path routing algorithm (SWP), the widest shortest path routing algorithm (WSP), and the max-min matching routing algorithm (MMRA). The SWP and WSP are found to have better performance than the existing algorithms. The MMRA is able to achieve a high probability of find feasible solution whenever one exists.